Modelling the potential for parenting skills interventions to reduce inequalities and population prevalence of children's mental health problems: Evidence from the Millennium Cohort Study - Steven Hope; Anna Pearce; Mario Cortina-Borja; Catherine Chittleborough; Jane Barlow; Catherine Law (Elsevier, 2021)
Parenting programmes can improve parenting quality and, in turn, children's mental health. If scaled-up, they have the potential to reduce population inequalities and prevalence in child mental health problems (MHP). However, this cannot be investigated with trials. Using data from the UK Millennium Cohort Study (18,000 children born 2000-2002), we simulated population impact of scale-up of seven parenting programmes. Predicted probabilities of child MHP (Strengths and Difficulties Questionnaire) by household income quintile (Risk ratios [RRs] and differences [RDs], 95% confidence intervals [CI]) were estimated from logistic marginal structural models, adjusting for parenting quality scores (Child-Parent Relationship Scale at 3 years) and confounders. The impact of scaling-up parenting programmes was simulated by re-estimating predicted probabilities of child MHP after increasing parenting scores according to intervention intensity, targeting mechanisms and programme uptake levels. Analyses included data from 14,399 children, with survey weights and multiple imputation addressing sampling design, attrition and item missingness. Prevalence of child MHP at 5 years was 11.3% (11.4% unadjusted), with relative and absolute income inequalities (RR = 4.8[95%CI:3.6-5.9]; RD = 15.8%[13.4-18.2]). In simulations, universal, non-intensive parenting programmes reduced prevalence (9.4%) and absolute inequalities (RR = 5.0[95%CI:3.8-6.2]; RD = 13.6%[11.5-15.7]). Intensive programmes, targeting a range of potential risk criteria (e.g. receipt of means-tested benefits), reduced inequalities (RR = 4.0[95%CI:3.0-4.9]; RD = 12.4%[10.3-14.6] and, to a lesser extent, prevalence (10.3%). By simulating implementation of parenting programmes, we show that universal non-intensive and targeted intensive approaches have the potential to reduce child MHP at population level, and to reduce but not eliminate inequalities, with important implications for future policy and practice.